Strategi Komunikasi Muhammadiyah dalam Menebar Dakwah Kultural Persfektif Muhammad Abu Fatah Al-Bayanuni (Studi Kasus: Muhammadiyah Bangun Purba Deli Serdang) - Syaifudin, Muhammad; Rasyid, Abdul (JURNAL LENSA MUTIARA KOMUNIKASI, 2023)
In this study the authors wanted to know the Communication Strategy of the Muhammadiyah Bangun Purba Branch Leaders in spreading cultural da'wah. The author uses Muhammad Abu Fatah Al-Bayanuni's Da'wah Strategy Theory, including: Athifiy Da'wah Strategy, Aqliy Strategy, and Hissiy Method. In this study the authors used descriptive qualitative research. In collecting data the authors used three techniques, namely: participant observation, in-depth interviews, and documentation. Data validity technique with credibility test. Data analysis techniques using the Miles & Huberman model. Muhammadiyah Bangun Purba Branch Manager has its own communication strategy in spreading cultural da'wah, in carrying out the tradition of the Seven Months of Pregnancy, it is more advisable for Persyarikatan residents to Al-Quran recitations during the pregnancy process without having to enter the seventh month of pregnancy. Whereas in the Tahlilan tradition of Sending Prayers for people who have died, the Muhammadiyah Bangun Purba Branch Leader forbade it to be carried out, Muhammadiyah Bangun Purba members prioritize the nature of respecting and maintaining friendship. To show the existence that Muhammadiyah is not anti-art culture, currently the Branch Manager Muhammadiyah Bangun Purba has a dance and Martial Arts studio, Tapak Suci.